2021
DOI: 10.3389/fgene.2021.680120
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Co-expression Network Analysis Identifies Key Genes Regulating Conchosporangia Maturation of Pyropia haitanensis

Abstract: Conchosporangia maturation is crucial for the yield of Pyropia/Porphyra. However, the molecular mechanisms underlying this process are poorly understood. In this study, we selected two strains of Pyropia haitanensis that show significant differences in conchosporangia maturation as materials to produce RNA-Seq libraries. Then, we identified key molecular pathways and genes involved in conchosporangia maturation by conducting a weighted gene co-expression network analysis. Two specific modules were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The PE, PC, and APC contents in the P. haitanensis conchocelis life cycle stage gradually increase under maturation-inducing conditions (e.g., LI as well as high temperatures and phosphorous levels). This increase helps cells maintain efficient light-harvesting activities under decreased light irradiance and duration [ 27 ]. In the present study, the PE, PC, and APC contents were higher in the P. haitanensis LIT strain than in the LIS strain under control and LI conditions ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The PE, PC, and APC contents in the P. haitanensis conchocelis life cycle stage gradually increase under maturation-inducing conditions (e.g., LI as well as high temperatures and phosphorous levels). This increase helps cells maintain efficient light-harvesting activities under decreased light irradiance and duration [ 27 ]. In the present study, the PE, PC, and APC contents were higher in the P. haitanensis LIT strain than in the LIS strain under control and LI conditions ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that the PI signaling system is important for the perception of external stimuli and the subsequent signal transduction in P. haitanensis [ 27 , 28 , 29 ]. In the present study, LI treatment resulted in the upregulated expression of key genes associated with the PI signaling system in both P. haitanensis strains, including genes encoding PLCD, PI4KB, PIK3C3, PIP5K, and DGK ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, filamentous sporophytes within the shell do not undergo direct meiotic division to form gametophytes. Instead, it takes months for them to produce conchosporangial branches, and only then do mature conchosporangia release conchospores ( Lin et al., 2021 ). Moreover, the conchosporangia do not result from enlargement of the original conchocelis cells; rather, they are newly produced from the conchocelis through tip growth via swelling of the apical cells of the conchocelis branch ( Taya et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%